The Effect of Executive Compensation and Managerial Ownership on Earnings Management with CEO Overconfidence as a Moderating Variable - Ni Luh Ayu Karningsih; Anak Agung Gde Putu Widanaputra; I Ketut Yadnyana; Ayu Aryista Dewi (Academic Bright Collaboration, 2026)
Purpose – This study examines the effect of executive compensation and managerial ownership on earnings management, and the moderating role of CEO overconfidence in these relationships within Indonesian non-financial firms. Methods – A quantitative approach was applied using 152 firm-year observations from Basic Materials, Consumer Cyclicals, Consumer Non-Cyclicals, Industrials, and Healthcare companies listed on the Indonesia Stock Exchange during 2021–2024. Purposive sampling was used. Earnings management was measured through discretionary accruals using the Modified Jones Model. Executive compensation was measured as the natural logarithm of top executive remuneration, managerial ownership as the natural logarithm of management share ownership, and CEO overconfidence as the capital expenditure to operating cash flow ratio. Data were analyzed using fixed-effects panel regression with firm-clustered standard errors. Findings – Executive compensation and managerial ownership negatively and significantly affect earnings management, confirming the alignment effect of agency theory. CEO overconfidence does not significantly moderate either relationship; both governance mechanisms remain effective regardless of CEO overconfidence. A supplementary binary overconfidence test shows that managerial ownership is measurement-sensitive. Research implications – The findings suggest that agency theory’s rational-manager assumption explains the direct effects of compensation and ownership. The non-significant moderation effects and measurement sensitivity imply that the interaction between psychological bias and governance mechanisms is context-dependent and proxy-specific. Future research should employ multiple overconfidence measures to define moderation boundaries. Originality – This study simultaneously tests two governance mechanisms and their interaction with CEO overconfidence in one Indonesian model, offering methodological and contextual insight rather than a definitive empirical claim.